2021
DOI: 10.1021/acsami.1c20128
|View full text |Cite
|
Sign up to set email alerts
|

Unsaturated NiII Centers Mediated the Coordination Activation of Benzylamine for Enhancing Photocatalytic Activity over Ultrathin Ni MOF-74 Nanosheets

Abstract: Creating accessible unsaturated active sites in metal− organic frameworks (MOFs) holds great promise for developing highly efficient catalysts. Herein, ultrathin Ni MOF-74 nanosheets (NMNs) with high-density coordinatively unsaturated Ni II centers are prepared as a photocatalyst. The results of in situ ATR−IR, Raman, UV−vis DRS, and XPS suggest that abundant Ni II centers can act as the active sites for boosting benzylamine (BA) activation via forming −Ni−NH 2 − coordination intermediates. The generation of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Subsequently, the •O 2 − species would oxidate PhCH 2 NH 2 •+ into phenylmethanimine (PheCH = NH) and then couple with other BA molecules to form N‐benzylidenebenzylamine product. [ 21 ]…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, the •O 2 − species would oxidate PhCH 2 NH 2 •+ into phenylmethanimine (PheCH = NH) and then couple with other BA molecules to form N‐benzylidenebenzylamine product. [ 21 ]…”
Section: Resultsmentioning
confidence: 99%
“…18 Wu and his co-workers also proved that the abundant NiII centers in MOF-74 can act as active sites for boosting benzylamine activation by forming –Ni–NH 2 – coordination intermediates. 19 It can be found that previous research studies on metal sites always focus on coordination activation but rarely combine this with coordination–photocatalysis synergism. Actually, MOFs are supposed to be credible platforms for researching the micro-mechanism of heterogeneous catalysis because of their explicit structure.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Much effort has been made to improve the efficiency of MOF photocatalysts including structural engineering, modication and functionalization. [14][15][16] Among these, defect engineering has been documented to be an effective approach to tailor the photocatalytic behavior. 17 Zr(IV)-based MOF UiO-66 has attracted extensive attention due to its ability to tolerate structural defects, discovered in 2011 by the discrepancy between the predicted and actual weight loss of thermogravimetric analysis disclosing a linker deciency in the Zr coordination shell.…”
Section: Introductionmentioning
confidence: 99%
“…11–13 Much effort has been made to improve the efficiency of MOF photocatalysts including structural engineering, modification and functionalization. 14–16 Among these, defect engineering has been documented to be an effective approach to tailor the photocatalytic behavior. 17…”
Section: Introductionmentioning
confidence: 99%